ROMANTISME SEBAGAI BENTUK ESTETIKA DALAM NOVEL HILMY MILAN KARYA NADIA RISTIVANI - Cindi Syaharani; Sri Wahono Saptomo; Sukarno ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2024)
This research aims to describe romanticism as a form of aesthetics in the novel Hilmy Milan by Nadia Ristivani. The problem discussed in this research is how the novel Hilmy Milan by Nadia Ristivani actualizes romanticism as a form of aesthetics. This research method uses a descriptive qualitative method with a literature study technique. The data is in the form of quotations that contain meaning about romanticism. The data source in this research is a novel entitled "Hilmy Milan" by Nadia Ristivani, the data collection technique is done by reading and recording techniques. Source triangulation, which involves examining various relevant sources to measure the reliability of research data, was used to verify the validity of the data. Qualitative descriptive technique was used to conduct data analysis, the data was analyzed to find the form of romanticism and presented along with its interpretation descriptively. The results of this study show that the novel "Hilmy Milan" by Nadia Ristivani has two different aspects of romance: the romance aspect and the expressive aspect. The romance aspect involves Hilmy and Milan, while the expressive aspect includes joy and sorrow, true love, loyalty, and achieving dreams.